Intelligent elderly care II - Low, Jia Xin. (2013)
Dementia in Singapore has been on the rise in recent years. In order to address the healthcare needs of dementia patients, this project focused on coming out with technological developments that can help in making life easier for people suffering from dementia and their caregivers in certain situations. A home monitoring system with an indoor positioning subsystem, a sensor feedback subsystem and an integrated website subsystem was designed and produced. After some market research, the Arduino platform was chosen to be the main platform of the system, as a result of its simplicity, portability and reliability. Digi International XBee modules, which make use of the low-power-consumption ZigBee technology, are the wireless transmitting modules implemented in this project. The PIR motion sensor and the XBee modules are powered up using a portable battery pack, which makes the indoor positioning system sensor nodes lightweight and portable. The few solutions redesigned in the development of the software also allowed the developer to gain insights into the various ways to implement this project.